2022
DOI: 10.1021/acs.jpclett.2c00228
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Asymmetric Splitting of Kondo Peak in Spin-Polarized Scanning Tunneling Spectroscopy: Insights from First-Principles-Based Simulations

Abstract: The spin-polarized scanning tunneling microscope (SP-STM) has served as a versatile tool for probing and manipulating the spintronic properties of atomic and molecular devices with high precision. The interplay between the local spin state and its surrounding magnetic environment significantly affects the transport behavior of the device. Particularly, in the contact regime, the strong hybridization between the SP-STM tip and the magnetic atom or molecule could give rise to unconventional Kondo resonance signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…31,66,67 Δ i ασ is extracted from the Kohn–Sham Green function with or without the coupled substrate (or tip). 30 The details are described in section S4 of the ESI †…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…31,66,67 Δ i ασ is extracted from the Kohn–Sham Green function with or without the coupled substrate (or tip). 30 The details are described in section S4 of the ESI †…”
Section: Resultsmentioning
confidence: 99%
“…[26][27][28][29] Recently, Zhuang et al used the DFT + HEOM method to reproduce the experimental phenomena reported by Choi's group 17 and proposed a co-tunnelling mechanism to explain the physical origin of asymmetric Kondo splitting. 30 Using the combined DFT + CASSCF + HEOM method, our group accurately simulated the spin state control induced by the STM tip in the FeOEP/Pb(111) adsorption system. 31 However, due to the complex interactions between the molecule and its environment, theoretical simulations of magnetictip-induced anomalous quantum behaviour in molecule/ surface adsorption systems remain limited.…”
Section: Introductionmentioning
confidence: 99%
“…52 These studies include Kondo transport, magnetic anisotropy manipulation, spin-polarized scanning tunneling spectroscopy and so on. [112][113][114][115] Furthermore, there would be a so-called dissipaton embedded quantum master equation formalism, with system-plus-dissipatons being all incorporated into a single master equation. This provides an alternative formalism for quantum simulations in both bosonic and fermionic scenarios.…”
Section: Concluding and Prospective Remarksmentioning
confidence: 99%
“…For the sake of numerical convenience, a Lorentzian function of the form normalΓ α ν ( ω ) = normalΓ α ν W α 2 false( ω normalΩ α false) 2 + W α 2 is adopted, where Γ αν is the effective hybridization strength between the νth d orbital on the Ni ion and the s bands in the αth reservoir and Ω α and W α are the band center and bandwidth of the αth reservoir, respectively. The involved energetic parameters (ϵ ν , U ν , Γ αν , W α , and Ω α ) are extracted from the DFT calculations ,,− (see section S3 of the Supporting Information for details). In particular, the magnitudes of s–d hybridization strength Γ αν are obtained by analyzing the Kohn–Sham Green’s functions. , The parametrized AIM is then solved by using the Fermionic HEOM method, which is capable of addressing the impurity–reservoir hybridization, electron transport, multielectron cotunneling, and strong correlation effect in a nonperturbative manner. ,, …”
mentioning
confidence: 99%
“…The involved energetic parameters (ϵ ν , U ν , Γ αν , W α , and Ω α ) are extracted from the DFT calculations ,,− (see section S3 of the Supporting Information for details). In particular, the magnitudes of s–d hybridization strength Γ αν are obtained by analyzing the Kohn–Sham Green’s functions. , The parametrized AIM is then solved by using the Fermionic HEOM method, which is capable of addressing the impurity–reservoir hybridization, electron transport, multielectron cotunneling, and strong correlation effect in a nonperturbative manner. ,, …”
mentioning
confidence: 99%